Original paperHigh-pressure plain balloon predilation preceding drug-eluting stent implantation for treatment of bare metal in-stent restenosis leads to better acute procedural results as compared to direct drug-eluting stenting. Volumetric Intravascular Ultrasound Study - Kalińczuk, Łukasz; Pręgowski, Jerzy; Witkowski, Adam; Dębski, Artur; Ciszewski, Andrzej; Chmielak, Zbigniew; Warmiński, Grzegorz; Kindop, Marcin; Tyczyński, Paweł; Bekta, Paweł; Karcz, Maciej; Przyłuski, Jakub; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2006)
Recurrent renarrowing after drug-eluting stent (DES) implantation for bare metal in-stent restenosis (ISR) is mostly the result of DES underexpansion. Whether the high-pressure plain balloon predilatation (group 1) preceding DES implantation for ISR treatment might lead to better acute procedural results as compared to the direct DES stenting (group 2) is unknown. Methods: Of all 61 treated ISR lesions pre- and postprocedural intravascular ultrasound (IVUS) examinations were done in consecutive 52 (85%) lesions. Strategy of DES implantation was operator dependent and angiography guided. Baseline angiographic and IVUS characteristics as well as procedural data were similar for both groups. Minimal lumen cross-sectional area after DES implantation (DES MA) and DES expansion index were bigger in group 1 (n=23, 44%) than in group 2 (6.5±1.6 mm 2 vs 5.5±2.0 mm 2 , p=0.013 and 106±50% vs 81±28%, p=0.030, respectively). High-pressure balloon predilatation was equally superior for restenosis in initially underex-panded (n=9, 17%) and adequately deployed stents (p=0.016 and p=0.039, respectively). Despite the optimal angiographic result in both groups, stent underexpansion defined as DES MA <5.0 mm 2 was present in 34.6% (n=18) of all lesions, with mean DES MA of 4.2±0.5 mm 2 . Interestingly, whereas significant DES underexpansion was documented in only 1 lesion from group 1 (4.3%), DES MA of <5.0 mm 2 was noted in 58.6% (n=17) of targets from group 2 (p <0.001). Conclusions: High-pressure plain balloon predilatation preceding DES implantation for ISR treatment results in bigger acute lumen gain and better DES expansion as compared to the direct DES stenting, regardless of the initial BMS expansion.